Delegating for business success - Chan, Janis Fisher (American Management Association, 2004)
Empower staff and the organization with savvy delegation skills for 21st-century success. Delegation has always been an essential supervisory and managerial competency. In today's lean, competitive workplace, it's a survival skill for organizational success. This lively new look at an old skill addresses today's delegation challenges with a workable plan and many practical exercises to ensure successful implementation. Discover what delegating really involves and learn to make confident delegating choices. Readers will learn how to: Respond rapidly to changing circumstances and employ time an.
Title from PDF title page (viewed Oct. 4, 2011). - Includes bibliographical references (pages 95-96) and index
Keywords: Delegation of authority; Delegation of authority -- Examinations, questions, etc; Management; Management -- Examinations, questions, etc; Success in business; Success in business -- Examinations, questions, etc; Délégation des pouvoirs (Gestion); Délégation des pouvoirs (Gestion); Examens, questions, etc; Gestion; Gestion; Examens, questions, etc; Succès dans les affaires; Succès dans les affaires; Examens, questions, etc; management; BUSINESS & ECONOMICS; Corporate Governance; BUSINESS & ECONOMICS; Leadership; BUSINESS & ECONOMICS; Organizational Development; BUSINESS & ECONOMICS; Workplace Culture; Examinations